O cuidado terapêutico com familiares de dependentes de álcool e outras drogas: uma revisão da literatura - Calia, Ararê Dias (2019)
The conduction of studies, with the objective of understanding the suffering and the interventions to the families of alcohol and drugs addicts who go through clinical therapeutic processes, shows itself increasingly more necessary. The theme of this research emerged during the clinical work. Since the beggining, we had sessions with patients that declared themselves as “relatives of chemical dependents”. This meant not only blood ties or matrimonial, but certain familiarity with some friend or acquaintance whose compulsive use of drugs had affected their relation, their world and their existence. The researches done in the last decades showed both an exploration of this phenomenon, from a biological, pragmatic and technical-scientific perspective, and well as under the aegis of of very specific schools of thought within the field of psychology. Therefore, anchored by existential phenomenology and it´s hermeneutics, having as a guiding question the development of a critical analysis, based on that thought, we investigated the the existing theorizations and propositions of clinical interventions focused into the care of relatives of drug addicts. We have done an empirical review from the productions about this theme, from the BVS-Psi Plataform, integrated to Scielo, between the period of 2013-2017, criteria of evaluation Qualis/Capes A1, A2, B1 and B2, published in Brazil. The research was conducted in two stages. In the first, the results didn´t align with the objectives sought in this research, so we choosed to exclude it´s results after reading the abstracts. We did a new search in the BVS-Psi Plataform, with a refinement of the key words, now more in tune with the objectives, and we selected four articles, that were used in our discussions and considerations. The studies showed that there isn´t an exclusive attention to the population of families of addicts, as a main “object” of care, but as part of the treatment of the addicts themselves. Such condition puts them as families of “subjection”, preventing the legitimization of their suffering in their own existential condition. We observed, therefore, a scientific gap in the understanding and intervention towards that population. Seeking to promote reflections and academic and social contributions to this field, specially in existential phenomenology, the current research was able to make explicit the necessity of other authors to focus into this theme and promote other reflections. This research was developed with finantial support from the National Council of Scientific and Technological Development (CNPq)